Study of the Use of Digital Technology in Preschool Education - Li, Ze (Transactions on Economics, Business and Management Research, 2024)
In today’s society, digital technology is penetrating into various industries and fields of life at an unprecedented speed, and the education industry, especially the field of preschool education, is no exception. The purpose of this paper is to explore and analyze the research on the application of digital technology in preschool education, to reveal the significance of its application in preschool education, the challenges it is currently facing and the strategies to cope with it, and to try to provide useful references for the practice and theory of preschool education digitalization.